Pengembangan Strategi Bisnis pada CV. XYZ Menggunakan Pendekatan Business Model Canvas - Ahmad Rizal Prayogo; Mohammad Sholihul Zain; Moch Noval Ilham Askafi; Retno Indriartiningtias (Metris: Jurnal Sains dan Teknologi, 2025)
The construction industry in Indonesia continues to grow but often faces inefficiencies in conventional construction methods. This study aims to analyze and develop a business strategy for CV. XYZ, a manufacturer of Rekabrick interlock bricks, using the Business Model Canvas (BMC) approach. The research methodology employed is descriptive qualitative and quantitative, with data obtained through direct observation and interviews with management regarding operational activities. The BMC mapping results indicate that CV. XYZ has a strong business foundation, particularly in its value proposition of project time and cost efficiency. However, this study formulates improvement strategies by expanding customer segments to include home improvement enthusiasts and interior designers, as well as optimizing digital channels through VR/AR preview features. The recommended strategies focus on market education and digitalization to expand market reach and ensure business sustainability amidst competitive industry pressure.